Determinants of Level of household income utilization and decision making among the educated working married employees in Mbarara Municipality, Mbarara, Uganda - Sanni, Tajudeen Adebayo (Advances in Social Sciences Research Journal, 2021)
The study determines the level of household income utilization and decision-making among educated working married employees in the Mbarara Municipality, Mbarara, Uganda. The study was guided by Sen’s Cooperative Conflict Theory. The study employed a mixed design of quantitative and qualitative approach. It targeted working educated married employees from MMC with a study sample of 113 respondents consisting of 92 married, educated working employees. Purposive sampling was used to select key informants (21) like the LCs 1,(6) 2(6) and 3(6) mayor,(1) probation officer(1) and legal officers (1) that is in the 6 division in the municipality was interviewed. Qualitative data were analyzed using themes and quantitative data using the Statistical Package for Social Sciences (SPSS) software. The study findings established that age, marital status, religion, educational qualification, years of marriage, monthly income influence the level of income utilization and decision-making among working educated married employees. In addition, patriarchal ideologies, community perceptions of decision making, gender roles, and religion also impacted their income utilization. The findings of this study also show that the level of household income utilization among the educated working married employees in Mbarara Municipality also varies based on the amounts earned by married employees and the difference between the husband and wife’s salaries. The study concluded that household income utilization in general significantly influences the decision making process and affect the level of income utilization among educated working married employees. This is because the household is a huge contributor to the decision making process in the majority of employees’ homes in Mbarara Municipality. Based on the findings, the study recommends that the government should intensify effort by providing jobs for men and women to meet the financial obligation in their household. Keywords: Gender Relations, Educated, Working Married Employees, Mbarara, Uganda